Dissolved Domoic Acid Does Not Improve Growth Rates and Iron Content in Iron-Stressed Pseudo-Nitzschia subcurvata - Geuer, Jana K.; Trimborn, Scarlett; Koch, Florian; Brenneis, Tina; Krock, Bernd; Koch, Boris P. (Frontiers in Marine Science, 2020)
Many regions of Antarctica are classified as high nutrient low chlorophyll (HNLC) areas. In these, iron availability is limiting primary productivity and subsequent carbon export. Domoic acid (DA) has previously been detected in the Southern Ocean and suggested to act as a ligand that facilitates iron assimilation for Pseudo-nitzschia spp., species that contribute to Antarctic diatom blooms. An incubation experiment using the Antarctic species Pseudo-nitzschia subcurvata was performed in Antarctic seawater at low and high iron concentrations. Dissolved DA was added to one set of each of the two treatments. This was done to verify whether DA positively affects the growth of the non-toxic species Pseudo-nitzschia subcurvata and increases its cellular iron content, particularly under low iron conditions. We hypothesize that (i) DA is taken up under low iron conditions (ii) that more iron is taken up if DA is available and (iii) that the growth rate increases in the presence of DA. We showed that P. subcurvata did not take up any added DA, even under low iron conditions. Additionally and contrary to our hypothesis, the cells were not positively influenced by the addition of dDA in terms of growth rate, cellular iron and carbon content. Hence, there was no significant difference in iron content between the different treatments. However, the cellular copper content increased under low iron conditions when DA was added. This study suggests that dissolved DA in naturally occurring concentrations does not increase bioavailability of iron to P. subcurvata and that only species producing DA might benefit from it.